Pengaruh Jamu Anemia terhadap Fungsi Ginjal di Rumah Riset Jamuâ€œHortus Medicusâ€ Tawangmangu - Ardiyanto, Danang; Triyono, Agus; Nisa, Ulfatun (Jurnal Farmasi Sains dan Terapan, 2015)
The use of herbal medicine in the formal health care requires adequate scientific evidence especially on herbal safety data. The herb could be used for the treatment of anemia. The indicator for the safety of the herb was kidney function by measuring urea and creatinine. A clinical trial study with pre-post test designed was conducted at the Jamu Research Center "Hortus Medicus" Tawangmangu to assess renal function of patients treated anemic with herbal formula for anemia. A total of 35 subjects volunteered to follow this study received therapy with herbal formula for 1 month. Formula was a herbal infusion made up of 5 grams of red amaranth leaves (Amaranthus tricolor L.), 10 grams herbs of tapak liman (Elephantopus scaber L.) and 15 grams of temulawak rhizome (Curcuma xanthorrhiza), taken 3 times a day. Kidney function was observed by measuring the levels of urea and creatinine subjects at baseline (D-0) and at day 28 (D-28). The results of t-test between urea levels in D-0 and D-28, showed the value of p = 0.942 (> 0.05) and creatinine levels in D-0 and D-28, p-value = 0.935 (> 0.05), which means no significant difference. It can be concluded that herbal formula for anemia did not affect renal function.